PERAN PEMBELAJARAN PENDIDIKAN PANCASILA DALAM MENGATASI FENOMENA CULTURE SHOCK PADA MAHASISWA UNIVERSITAS SYIAH KUALA YANG MENGIKUTI PROGRAM PERTUKARAN MAHASISWA MERDEKA - Pirdausi, Winsyam; Ruslan; Fahmi, Rizal (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The Independent Student Exchange Program provides students with opportunities to study in different social and cultural environments. However, differences in language, customs, cultural values, and communication patterns may cause culture shock and affect students’ adaptation processes. This study aims to examine the role of Pancasila Education in helping students of Syiah Kuala University adapt to new environments and overcome culture shock, as well as to describe their experiences in facing this phenomenon during participation in the Independent Student Exchange Program. This research employed a qualitative approach with a descriptive design. The participants consisted of eight Syiah Kuala University students who had participated in the second, third, and fourth cohorts of the program. Data were collected through in-depth interviews, observation, and documentation, and analyzed using data reduction, data display, conclusion drawing, and verification. The findings reveal that Pancasila Education plays an important role in overcoming culture shock through the strengthening of the values of Divinity, Humanity, Unity, Democracy, and Justice, which are reflected in tolerance, empathy, respect for diversity, deliberation, and awareness of rights and obligations. Students experienced culture shock mainly at the beginning of the program due to differences in language, dialects, customs, and communication styles. Nevertheless, through social interaction, openness, and the application of Pancasila values, students were able to adapt to the new environment and develop harmonious social relationships.